2020
DOI: 10.7554/elife.48361
|View full text |Cite
|
Sign up to set email alerts
|

Direct glia-to-neuron transdifferentiation gives rise to a pair of male-specific neurons that ensure nimble male mating

Abstract: Sexually dimorphic behaviours require underlying differences in the nervous system between males and females. The extent to which nervous systems are sexually dimorphic and the cellular and molecular mechanisms that regulate these differences are only beginning to be understood. We reveal here a novel mechanism by which male-specific neurons are generated in Caenorhabditis elegans through the direct transdifferentiation of sex-shared glial cells. This glia-to-neuron cell fate switch occurs during male sexual m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 90 publications
0
24
0
Order By: Relevance
“…On the more speculative side, the generation of an additional cell to make a DVB motor neuron might be under positive selection pressure since the K cell is a non-redundant structural part of the rectal tube, a vital organ (Sulston et al, 1983; this study). In support to this hypothesis, the Td of the rectal Y cell (Jarriault et al, 2008), or of the phasmid socket PHso1 (Molina-Garcıa et al, 2020), which occurs in absence of cell division, also occurs while other cells, P12.pa and PHso2 respectively, will replace functionally the transdifferentiating cell. By contrast, no other cell replaces the AMso amphid socket, which conversion involves a cell division - although its importance for the cell conversion is not known (Sammut et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the more speculative side, the generation of an additional cell to make a DVB motor neuron might be under positive selection pressure since the K cell is a non-redundant structural part of the rectal tube, a vital organ (Sulston et al, 1983; this study). In support to this hypothesis, the Td of the rectal Y cell (Jarriault et al, 2008), or of the phasmid socket PHso1 (Molina-Garcıa et al, 2020), which occurs in absence of cell division, also occurs while other cells, P12.pa and PHso2 respectively, will replace functionally the transdifferentiating cell. By contrast, no other cell replaces the AMso amphid socket, which conversion involves a cell division - although its importance for the cell conversion is not known (Sammut et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…It remains to be seen if these factors are involved in other natural reprogramming events, or if region or tissue-specific variations exist. Interestingly, a recent study reported a low penetrance defect in mosaic animals having lost a sox-2 rescuing array, although using systemic RNAi the sem-4 and sox-2 genes appeared little or not involved, in the AMso-to-MCM or the PHso-to-PHD conversions (Molina-Garcıa et al, 2020). This study together with the present one underscore the importance of the approach used to eliminate sox-2 activity, since we found that sox-2 systemic RNAi, even in a sensitized background, did not result in significant K-to-DVB defects by contrast with cell-specific expression of a sox-2 antisense.…”
Section: Discussionmentioning
confidence: 99%
“…C. elegans males also display differences in sexual conditioning of associative learning (Sakai N et al 2013). Interestingly, two of the male-specific neurons required for this behavior are derived from glia (SAMMUT et al 2015;MOLINA-GARCIA et al 2020). A recent study employed quantitative computation strategies to compare the circuitry of the nerve ring and ganglia in the head for both sexes (COOK et al 2019).…”
Section: Advances In Connectomicsmentioning
confidence: 99%
“…Of the 302 neurons that hermaphrodites of C. elegans possess, 60 are ciliated. Males have an additional 54 ciliated neurons that are not present in hermaphrodites (Inglis et al., 2007; Molina‐García et al., 2019). All cilia in C. elegans are present at the tips of dendrites and some cilia are exposed to the environment.…”
Section: Elegans Sensory Neurons As a Model To Study Ciliary Mtsmentioning
confidence: 99%